PERLAKUAN AKUNTANSI ATAS BIAYA PINJAMAN PADA INDUSTRI PROPERTI MELALUI KREDIT PERBANKAN BERDASARKAN PSAK 26 (REVISI 2012) - Rolihlahla, Ghusti Ayu Criestiant (Jurnal Akuntansi AKUNESA, 2014)
According to SFAS 26, the loan costs that could directly attributable are theacquisition for construction or the manufacture of qualifying assets, whereas thefinancial assets and inventories which is manufactured or produced in the shortterm does not include as a qualifying assets. For the assets which is ready for useor sale when acquired in accordance with the intention when acquired are notinclude as a qualifying assets, thus the loan costs are recognized immediately ascost in the current period. It ussualy happended in property industry wheres thatindustry use the loan fo the capital building. The properties give an economicstrongnese in the future.Keywords: loan costs, qualifying assets, property.